2019
DOI: 10.1111/pedi.12863
|View full text |Cite
|
Sign up to set email alerts
|

A labile form of hemoglobin A1c is higher in African‐American youth with type 1 diabetes compared to Caucasian patients at similar glucose levels

Abstract: Background Hemoglobin A1c (HbA1c) levels are higher in African‐American (AA) individuals compared to Caucasians (EA) even after adjustment for blood glucose levels. To better understand the mechanism of this disparity we examined the relationship of an unstable (labile) form of HbA1c (L‐HbA1c) with race and glucose. Methods Samples for HbA1c were collected from pediatric patients self‐identified as either AA (15F, 12M, age 13.4 ± 3.5 years) or EA (22F, 30M, age 14.6 ± 3.4 years) with type 1 diabetes at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The average HbA1c level in another AA population was comparatively higher than that of the Caucasian population 41 . HbA1c not only provides a reliable measure of chronic hyperglycemia but also correlates well with the risk of long‐term diabetes complications 42 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The average HbA1c level in another AA population was comparatively higher than that of the Caucasian population 41 . HbA1c not only provides a reliable measure of chronic hyperglycemia but also correlates well with the risk of long‐term diabetes complications 42 .…”
Section: Discussionmentioning
confidence: 96%
“…The average HbA1c level in another AA population was comparatively higher than that of the Caucasian population. 41 HbA1c not only provides a reliable measure of chronic hyperglycemia but also correlates well with the risk of long-term diabetes complications. 42 The suboptimal management of HbA1C level is assumed to be caused by biological, socioeconomic, and quality-of-care-related variables.…”
Section: Bmi and Relative Gene Expression Over The Diabetes Populationmentioning
confidence: 99%
“…21,41,42 The concentrations of the biochemical precursor to clinically measured HbA1c, labile HbA1c, has also been found to be higher in NHB vs NHW youth, suggesting differences in the internal RBC environment as a possible underlying cause of this phenomenon. 43 Factors influencing HbA1c concentration such as variation in RBC indices and iron content do not appear to underlie MBG-independent racial disparity in HbA1c. 44,45 Some investigators have suggested differences in intracellular glucose, red cell longevity, and deglycating enzymes as possible mechanisms.…”
Section: Obstacles To Achieving Optimal Control With Type 1 Diabetesmentioning
confidence: 98%